Indonesia's regional diplomacy : imperative to maintain Asean cohesion - Sebastian, Leonard C (2012)
Indonesia’s more aggressive stance in regional diplomacy following ASEAN’s failure to reach a consensus at last week’s ASEAN Ministerial Meeting (AMM) is motivated by its desire to maintain regional cohesion and autonomy. How does Indonesia view itself in terms of regional groupings like ASEAN?